On the Sum and Product of Covering Numbers of Graphs and their Line Graphs - ., Susanth C; Kalayathankal, Sunny Joseph (Communications in Mathematics and Applications, 2015)
The bounds on the sum and product of chromatic numbers of a graph and its complement are known as Nordhaus-Gaddum inequalities. In this paper, we study the bounds on the sum and product of the covering numbers of graphs and their line graphs. We also provide a new characterization of the certain graph classes.